2008
DOI: 10.1111/j.1471-4159.2008.05339.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel calcium‐binding protein is associated with tau proteins in tauopathy

Abstract: Tauopathies are a group of neurological disorders characterized by the presence of intraneuronal hyperphosphorylated and filamentous tau. Mutations in the tau gene have been found in kindred with tauopathy. The expression of the human tau mutant in transgenic mice induced neurodegeneration, indicating that tau plays a central pathological role. However, the molecular mechanism leading to tau-mediated neurodegeneration is poorly understood. To gain insights into the role that tau plays in neurodegeneration, hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(132 citation statements)
references
References 34 publications
7
125
0
Order By: Relevance
“…Whereas NF-AT has not been studied so far, we showed already that Swip-1 blocks expression of the antiapoptotic NF-kB target gene bclxL (22). An explanation could be that Swip-1 binds calcium directly (27) and is therefore part of a negative feedback loop. Because Swip-1 blocks NF-kB in WEHI231 cells (22), we propose that Swip-1 rather counteracts tonic BCR survival signaling (72), despite inducing constitutive membrane raft association of Syk, PLCg2, and the mHC in WEHI231 cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Whereas NF-AT has not been studied so far, we showed already that Swip-1 blocks expression of the antiapoptotic NF-kB target gene bclxL (22). An explanation could be that Swip-1 binds calcium directly (27) and is therefore part of a negative feedback loop. Because Swip-1 blocks NF-kB in WEHI231 cells (22), we propose that Swip-1 rather counteracts tonic BCR survival signaling (72), despite inducing constitutive membrane raft association of Syk, PLCg2, and the mHC in WEHI231 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Swip-1 targets PLCg2 and Syk to membrane rafts likely in an SLP-65-independent manner, although we cannot exclude involvement of (53), and it can possibly associate with microtubule-associated tau proteins (27). In that sense, it has been suggested that a-and b-tubulin stably associate with RhoH, which, in turn, associates stably with Syk and PLCg2 (54), and Syk has been shown to associate with microtubules (55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point in this direction is the recently described resistance of hippocampal neurons expressing the calcium-binding protein secretagogin (SCGN) to neurodegeneration (Attems et al 2008). The parallel involvement of calcium-binding proteins and TAU, which is suggested by these data, was underlined by the recently described interaction of a novel EF-hand calcium-binding protein and TAU in the CNS (Vega et al 2008).…”
Section: Introductionmentioning
confidence: 89%
“…It has been shown that pyramidal neurons at the hippocampus expressing SCGN are greatly free of hyperphosphorylated TAU deposits (Attems et al 2008), and TAU was shown to interact with other members of the EF-hand calcium-binding protein family in mouse brain (Vega et al 2008). The calcium-binding protein SCGN has been demonstrated to be highly and specifically expressed within the islets of Langerhans (Wagner et al 2000, Cras-Meneur et al 2004.…”
Section: Tau Associated With Scgn In Rin-5f Cellsmentioning
confidence: 99%